Lipoprotein (a) levels in children with heterozygous familial hypercholesterolemia - Liliya F. Galimova; Dinara I. Sadykova; Evgeniia S. Slastnikova; Chulpan D. Khaliullina; Karina R. Salakhova (КардиоСоматика)
BACKGROUND: Recent studies show that lipoprotein (a), or Lp(a), plays a specific role in the development of atherosclerosis. Lp(a) promotes atherogenesis by increasing production of pro-inflammatory cytokines and depositing on the arterial wall. There are limited studies of Lp(a) in children with familial hypercholesterolemia (FH), and the results are not specified by age.